2020
DOI: 10.11591/ijai.v9.i2.pp290-296
|View full text |Cite
|
Sign up to set email alerts
|

Classification of tomato leaf diseases using MobileNet v2

Abstract: <span lang="EN-US">Tomato is a red-colored edible fruit originated from the American continent. There are a lot of plant diseases associated with tomatoes such as leaf mold, late blight, and mosaic virus. Tomato is an important vegetable crop that contributes to the world economically. Despite tremendous efforts in plant management, viral diseases are notoriously difficult to control and eradicate completely. Thus, accurate and faster detection of plant diseases is needed to mitigate the problem at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 19 publications
0
38
1
7
Order By: Relevance
“…Hence our proposed method has automated the feature extraction process and reduced the time extraction. In contrast, the deep learning methods used by Zaki et al [20], Agarwal et al [21] and Nithish et al [25] showed classification accuracy comparable to our methods.…”
Section: Results Evaluation and Analysiscontrasting
confidence: 48%
“…Hence our proposed method has automated the feature extraction process and reduced the time extraction. In contrast, the deep learning methods used by Zaki et al [20], Agarwal et al [21] and Nithish et al [25] showed classification accuracy comparable to our methods.…”
Section: Results Evaluation and Analysiscontrasting
confidence: 48%
“…Thirdly, apply the knowledge of ensemble algorithms, tuning of hyper parameters and diversity of pooling operations [19]. Fourthly, the prediction system needs enormous resources if the prediction was based on deep learning methodologies [25]. So, there is a significance to develop squeeze models to run the application in mobile phones, drones, UAVs and robots.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Mobilenet is a streamlined architecture that uses depthwise separable convolutions. The result of this architecture is a lightweigth CNN model that is efficient for mobile and embedded device application [1], [20][21][22]. Mobilenet uses 3x3 depthwise separable convolution reducing the computation to 8to 9 times less than the standard convolutions with the price of only small reduction in accuracy.…”
Section: Mobilenetmentioning
confidence: 99%